Critical Review on Financial Reporting Practices by Islamic Banks: (Comparison between AAOIFI and IFRS) - Perwiragama, Salman Abdurrubi; Fauziyah, Tias Rahmi (Nurani, 2022)
This paper summarizes the findings of a comparative critical examination of the financial reporting methods of Bank Al-Barakah, BTPN Syariah, and Maybank Islamic Berhad. Due to the discrepancy between theory and practice, several past studies have found that Islamic banks need to alter the implementation of their financing facilities. This fact requires clarification. The research employs the quantitative descriptive method and theoretical with secondary data sources derived from literature research, as well as the IASB Conceptual Framework, AAOIFI Conceptual Framework, Resolution 2 of the Sharia Advisory Committee of Bank Negara Malaysia (SAC BNM), Statement of Islamic Financial Accounting Standards (PSAK Syariah), and other related references. The findings of this study indicate that AAOIFI and IFRS interpret the objectives of financial reporting differently. AAOIFI serves sharia principles as an intrinsic component of financial reporting, whereas IFRS implements neutrality of financial reporting from religion or standard components. Overall, the authors of this article maintain that Islamic banks conform to AAOIFI criteria for all of its components, including financial reporting objectives, key accounting assumptions, and SLM-based revenue estimation.